Sound-Induced Activity in Voice-Sensitive Cortex Predicts Voice Memory Ability - Watson, Rebecca; Latinus, Marianne; Bestelmeyer, Patricia E. G.; Crabbe, Frances; Belin, Pascal (Frontiers in Psychology, 2012)
The ‘temporal voice areas’ (TVAs) (Belin et al., 2000) of the human brain show greater neuronal activity in response to human voices than to other categories of nonvocal sounds. However, a direct link between TVA activity and voice perception behaviour has not yet been established. Here we show that a functional magnetic resonance imaging (fMRI) measure of activity in the TVAs predicts individual performance at a separately administered voice memory test. This relation holds when general sound memory ability is taken into account. These findings provide the first evidence that the TVAs are specifically involved in voice cognition.